Role of the regulator in enabling a just culture: a qualitative study in mental health and hospital care - Roland Bal; Ian Leistikow; Jan-Willem Weenink; Iris Wallenburg; Guy Widdershoven; Laura Hartman; Eva van Baarle (BMJ Open)
Objectives A just culture is considered a promising way to improve patient safety and working conditions in the healthcare sector, and as such is also of relevance to healthcare regulators who are tasked with monitoring and overseeing quality and safety of care. The objective of the current study is to explore the experiences in healthcare organisations regarding the role of the healthcare inspectorate in enabling a just culture.Design Qualitative study using interviews and focus groups that were transcribed verbatim, and observations of which written reports were made. Transcripts and observation reports were thematically analysed.Setting Three mental healthcare providers, two hospitals and the healthcare inspectorate in the Netherlands.Participants We conducted 61 interviews and 7 focus groups with healthcare professionals, managers and other staff in healthcare organisations and with inspectors. Additionally, 27 observations were conducted in healthcare organisations.Results We identified three themes in our data. First, professionals and managers in healthcare organisations perceive the inspectorate as a potential catalyst for learning processes, for example, as an instigator of investigating incidents thoroughly, yet also as a potential barrier as its presence and procedures limit how open employees feel they can be. Second, a just culture is considered relational and layered, meaning that relationships between different layers within or outside the organisation might hinder or promote a just culture. Finally, for inspectors to enable a just culture requires finding a balance between allowing organisations the time to take responsibility for quality and safety issues, and timely regulatory intervention when healthcare providers are unwilling or unable to act.Conclusions If regulators intend to enable the development of a just culture within healthcare organisations, they must adopt regulatory procedures that support reflection and learning within the organisations they regulate and consider mutual trust as a vital regulatory tool.